Renal hyperfiltration with and without metabolic syndrome: differential implications for cardiovascular events, kidney failure, and mortality - Lee, Yu Ho; Kim, Dae Kyu; Kim, Jin Sug; Jeong, Su Jin; Jeong, Kyung Hwan; Hwang, Hyeon Seok (Frontiers in Nutrition, 2025)
BackgroundRenal hyperfiltration (RHF) and metabolic syndrome (MetS) share common pathophysiology and are both associated with adverse clinical outcomes. However, their combined impact remains unclear.MethodsIn total, 278,552 propensity score-matched individuals were enrolled in the Korean National Health Insurance Service database (2009–2011). Participants were divided into four groups based on RHF and MetS status, and cardiovascular (CV) events, end-stage kidney disease (ESKD) progression, and all-cause mortality were evaluated.ResultsCompared to non-MetS with normal renal filtration (NRF), MetS with NRF was associated with a significant increase in the risk of CV events, which was further amplified when combined with RHF (adjusted HR = 1.44, 95% CI = 1.35–1.55, P for interaction = 0.047). Patients with RHF exhibited more pronounced increases in the HRs for CV events than those with NRF as the number of dysfunctional metabolic components increased (P for interaction = 0.019). The risk of ESKD progression was not increased in non-MetS with RHF; however, it was significantly higher in patients with MetS alone and highest in those with both MetS and RHF (adjusted HR = 3.23, 95% CI = 1.61–6.47). The risk of all-cause mortality was elevated in patients with RHF or MetS alone and highest in those with both RHF and MetS (adjusted HR = 1.41, 95% CI = 1.31–1.52).ConclusionThe clinical significance of RHF differs based on MetS status, with their coexistence posing the highest risk for CV events, ESKD progression, and all-cause mortality. A synergistic interaction between RHF and MetS was evident in the risk of CV events.